Essentials of library classification - Shah, Farooq Ahmad (New Delhi Rajat Publications, 2024)
There are many standard system of library classification in use, many more have been proposed over the years. However, in general classification systems can be divided inti three types depending on their use, viz., universal schemes, specific classification schemes and national schemes.
Keywords: Library and Information Science; Library Classification